Vanishing adrenal mass. (24th March 2011) - Bhansali, Anil; Ajithkumar, B V; Walia, Rama; Rajwanshi, A; Shanmugasundar, G; Shah, Viral
Abstract : Adrenal involvement by primary lymphomatous disorders is quite rare. Primary adrenal lymphoma is usually associated with bilateral adrenal involvement and presents as adrenal insufficiency or class B symptoms. The authors report a case who presented with pain in the abdomen and was diagnosed to have unilateral primary adrenal lymphoma. The patient responded to chemotherapy with near-complete resolution of the adrenal mass.